Design and Performance of Ultrathin Overlay Epoxy-Rubber Concrete - Qi Huang; Fei Chen (Advances in Materials Science and Engineering)
Epoxy-rubber concrete has a big potential to be used for pavement overlays, but there is currently no appropriate epoxy-rubber concrete design method and process. To explore the reasonable mix design process of epoxy-rubber concrete, the ultrathin overlay aggregate gradation and epoxy resin binder with high toughness and durability were selected to carry out the design process investigation of epoxy-rubber concrete. The performance of epoxy-rubber concrete was characterized by vibration compaction, repeated load CBR, porosity, Fort Kentucky, uniaxial compression, bending, rutting, antiskid performance, and noise-reduction performance test. Firstly, the optimum range of the rubber powder replacement rate was determined based on the porosity and deformation characteristics of the aggregate mixture. Then, the amount of epoxy resin binder was further determined based on the porosity and antistripping performance of the epoxy-rubber concrete. Finally, the mechanical properties, road performance, and functions of epoxy-rubber concrete were comprehensively considered to determine the optimum rubber power replacement rate obtaining the composition design of epoxy-rubber concrete. The results showed that adding rubber powder decreased the elastic modulus and plastic deformation of the mineral structure, enhancing the suitability of the mixture for flexible road pavements. However, when the replacement rate increased to a specific range, the rubber particles significantly interfered with the mineral material, worsening the stability of the structure. Therefore, it was preliminarily determined that the reasonable replacement rate of rubber powder was 30–50%. The ultrathin overlay epoxy-rubber concrete exhibited excellent antistripping performance, and its porosity increased with the epoxy resin dosage. The optimum epoxy content was 6.5% at 4.17% porosity. Within the preliminarily determined replacement rate range of rubber particles, as the replacement rate increased, the flexibility, high-temperature stability, antiskid performance, and shock and noise resistance of the mixture increased, but the compressive and flexural tensile strength values decreased. The integrated properties of the ultrathin overlay epoxy-rubber concrete indicated that the best replacement rate of rubber powder was 45%. In this paper, the replacement rate range of the rubber powder was initially determined based on the gradation composition of the mixture, which avoids blind determination of the replacement rate. And the composition of the concrete was obtained comprehensively by the performance and function of the epoxy-rubber concrete, which is reasonable and reliable. The epoxy-rubber concrete design method proposed in this paper can promote the application the epoxy-rubber concrete in pavement overlay engineering.